Davis advantage for psychiatric mental health nursing - Townsend, Mary C., 1941-; Morgan, Karyn I. (Philadelphia, PA : F.A. Davis Company, 2021)
"As it has been with each new edition of Psychiatric Mental Health Nursing: Concepts of Care in Evidence-Based Nursing, the goal of this tenth edition is to bring to practicing nurses and nursing students the most up-to-date information related to neurobiology, psychopharmacology, and evidence-based nursing interventions. This edition includes changes associated with the latest( fifth) edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-5)"--
Mary C. Townsend's name appears first in the previous edition
Includes bibliographical references and index
Keywords: Psychiatric nursing; Evidence-based nursing; Psychiatric Nursing -- methods; Mental Disorders -- nursing; Evidence-Based Nursing